A Multicenter Retrospective Cohort Study of Pregnancy Outcomes in Idiopathic Oligohydramnios at Term - Gao H; Tao H; Zou L; Luo QQ; Zhang WY (International Journal of Women's Health, 2025)
Hui Gao,1 Hui Tao,1 Li Zou,1 Qing-Qing Luo,1,2 Wei-Yuan Zhang3 1Department of Obstetrics and Gynecology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Obstetrics and Gynecology, Peking University International Hospital, Beijing, People’s Republic of China; 3Department of Obstetrics, Beijing Obstetrics and Gynecology Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Hui Tao; Li Zou, Department of Obstetrics and Gynecology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277 Jiefang Avenue, Wuhan, 430022, People’s Republic of China, Email taohui@hust.edu.cn; xiehezouli@hust.edu.cnObjective: The effect of idiopathic oligohydramnios or isolated oligohydramnios on perinatal outcomes at term pregnancies is understudied. This study aimed to show the current epidemiological status of idiopathic oligohydramnios in mainland China, evaluate the pregnancy outcomes, and discuss the optimal delivery opportunity and mode.Methods: We conducted a retrospective cohort study of 106,225 term pregnancies from 37 hospitals in mainland China. All cases that delivered a non-anomalous singleton fetus between 37+0 and 41+6 weeks were collected. Perinatal outcomes of different gestational weeks and different delivery modes were compared between the idiopathic oligohydramnios group and the control group.Results: The incidence of idiopathic oligohydramnios in singleton pregnancies at term was 2.6%. Compared with control pregnancies, the idiopathic oligohydramnios group was characterized by lower birth weights and higher cesarean section rates (P < 0.01, respectively). From early-term and full-term to late-term, a pregnancy with idiopathic oligohydramnios exhibited the trend of lower risk of cesarean delivery and neonatal intensive care unit (NICU) admission but a higher risk of meconium-stained amniotic fluid, non-reassuring fetal heart rate status (NRFHRS), and emergency cesarean delivery (P < 0.01, respectively). Notably, the rate of Apgar score < 7 at 5 min and cesarean section was the lowest when delivery occurred during the 39+0 to 40+6 weeks. There was a higher incidence of NRFHRS in the idiopathic oligohydramnios vaginal delivery group when compared to the selective cesarean section group (2.6% vs 1.2%, P=0.05), but with no significant differences in postpartum hemorrhage, low Apgar score, or NICU admission.Conclusion: The incidence of adverse pregnancy outcomes is higher in the idiopathic oligohydramnios group than in the control group. Adverse outcomes seem lowest in the group of vaginal delivery during the 39+0 to 40+6 weeks, but close intrapartum surveillance and active intervention still need to be applied.Keywords: idiopathic oligohydramnios, term pregnancy, pregnancy outcome, delivery mode, delivery opportunity